一种基于矩阵控制的船用岸电电源系统及其控制方法 (2019)
本发明涉及一种基于矩阵控制的船用岸电电源系统及其控制方法，所述系统包括功率变换单元，接收功率单元驱动器的触发信号，实现对岸电电源输入整流-逆变控制；功率单元驱动器，用于接收单元控制器转发的PWM控制指令，实现对功率变换单元的统一PWM触发控制；单元控制器，用于采集信号的信号调理及控制保护动作触发，并转发中央控制器的PWM指令至功率单元驱动器；中央控制器，用于实现岸电电源系统的系统控制，通过控制算法，发出PWM控制指令，并通过光纤发送至单元控制器；滤波装置，对岸电电源输入或输出进行滤波处理，满足岸电电源对供电谐波的要求。本发明技术方案实现岸电电源容量的灵活配置，提高电源供电可靠性。 The invention relates to a marine shore power source system based on matrix control and a control method thereof. The system comprises a power conversion unit, a power unit driver, a unit controller, a central controller and a filtering device, wherein the power conversion unit is used for receiving a trigger signal of the power unit driver to realize input rectification and inverting control for a shore power source; the power unit driver is used for receiving a PWM control command transmitted by the unit controller to realize unified PWM trigger control for the power conversion unit; the unit controller is used for collecting signal conditioning and control protection action trigger of the signal and transmitting the P